3-D GPS velocity field and its implications on the present-day post-orogenic deformation of the Western Alps and Pyrenees - H. N. Nguyen; P. Vernant; S. Mazzotti; G. Khazaradze; E. Asensio (Solid Earth, 2016)
We present a new 3-D GPS velocity solution for 182 sites for the region encompassing the Western Alps, Pyrenees, and southern France. The velocity field is based on a Precise Point Positioning (PPP) solution, to which we apply a common-mode filter, defined by the 26 longest time series, in order to correct for network-wide biases (reference frame, unmodeled large-scale processes, etc.). We show that processing parameters, such as troposphere delay modeling, can lead to systematic velocity variations of 0.1–0.5 mm yr −1 affecting both accuracy and precision, especially for short (< 5 years) time series. A velocity convergence analysis shows that minimum time-series lengths of ∼ 3 and ∼ 5.5 years are required to reach a velocity stability of 0.5 mm yr −1 in the horizontal and vertical components, respectively. On average, horizontal residual velocities show a stability of ∼ 0.2 mm yr −1 in the Western Alps, Pyrenees, and southern France. The only significant horizontal strain rate signal is in the western Pyrenees with up to 4 × 10 −9 yr −1 NNE–SSW extension, whereas no significant strain rates are detected in the Western Alps (< 1 × 10 −9 yr −1 ). In contrast, we identify significant uplift rates up to 2 mm yr −1 in the Western Alps but not in the Pyrenees (0.1 ± 0.2 mm yr −1 ). A correlation between site elevations and fast uplift rates in the northern part of the Western Alps, in the region of the Würmian ice cap, suggests that part of this uplift is induced by postglacial rebound. The very slow uplift rates in the southern Western Alps and in the Pyrenees could be accounted for by erosion-induced rebound.